2011
DOI: 10.1350/ijps.2011.13.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Violence, Debriefing and Increased Alcohol Consumption among Police Officers

Abstract: Purpose: this study examined the associations between increased alcohol consumption and work-related violence among police officers. Data consisted of a representative sample of Finnish police officers (N = 1,734), who responded anonymously to a postal questionnaire. Methods: binary logistic regression analyses were used to calculate the odds ratios and their 95 per cent confidence intervals (CIs) for increased alcohol consumption. Results: 5 per cent of the study group rated that they had increased their alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…exposure to violence at work, exposure to people in pain or distress, etc.) that they were hoping the alcohol would take away (Leino, Eskelinen, Summala, & Virtanen, 2011). This is typically the case with smoking as well.…”
Section: Coping Strategy: Alcohol and Tobacco Usementioning
confidence: 95%
“…exposure to violence at work, exposure to people in pain or distress, etc.) that they were hoping the alcohol would take away (Leino, Eskelinen, Summala, & Virtanen, 2011). This is typically the case with smoking as well.…”
Section: Coping Strategy: Alcohol and Tobacco Usementioning
confidence: 95%
“…In our earlier study we interviewed police officers and found that some of them had a fear of future violence [Leino et al, 2011]. To obtain a quantitative measure of the fear of future violence we elicited “Fear of future violence” by asking: “Are you afraid of possible future violence at work?” with response alternatives: 1 = not at all; 2 = a little; 3 = somewhat; 4 = a lot; and 5 = extremely.…”
Section: Methodsmentioning
confidence: 99%
“…In our earlier study, we showed an association between the occurrence of work‐related violence and increased alcohol consumption in a sample of police officers in Finland [Leino et al, 2011]. However, there appear to be no reports on whether more frequent exposure to violence, or more serious consequences of violence, are associated with increased adverse mental health and alcohol use, or on whether there is a possible dose–response pattern between injuries caused by work‐related violence and symptoms of adverse mental health and alcohol use among police officers.…”
Section: Introductionmentioning
confidence: 99%
“…In support of the relevance of these possible healthy coping mechanisms for police officers, past research has documented associations between police stressor and exercise (Norvell & Belles, 1993), sleep (Vila, 1996), support from fellow officers (Gershon et al, 2009) and religiosity (Beehr et al, 1995). Past research has also found associations between police stressors and the more unhealthy coping mechanisms of alcohol consumption (Beehr et al, 1995;Gershon et al, 2009;Ballenger et al, 2011;Leino et al, 2011;Violanti et al, 2011;Menard & Arter, 2013) and repressing emotions (Anderson & Lo, 2011), especially anger ('act as if nothing is bothering you': Gershon et al, 2009: 279;Ivie & Garland, 2011).…”
Section: Negative Outcomes Associated With Police Stressors and Possimentioning
confidence: 99%